Agreement between clinical and laboratory methods assessing tonic and cross‐link components of accommodation and vergence. (September 2015) - Neveu, Pascaline; Priot, Anne‐Emmanuelle; Philippe, Matthieu; Fuchs, Philippe; Roumes, Corinne
Abstract Background Several tests are available to optometrists for investigating accommodation and vergence. This study sought to investigate the agreement between clinical and laboratory methods and to clarify which components are actually measured when tonic and cross‐link of accommodation and vergence are assessed. Methods Tonic vergence, tonic accommodation, accommodative vergence (AC/A) and vergence accommodation (CA/C) were measured using several tests. Clinical tests were compared to the laboratory assessment, the latter being regarded as an absolute reference. The repeatability of each test and the degree of agreement between the tests were quantified using Bland‐Altman analysis. Results The values obtained for each test were found to be stable across repetitions; however, in most cases, significant differences were observed between tests supposed to measure the same oculomotor component. Tonic and cross‐link components cannot be easily assessed because proximal and instrumental responses interfere with the assessment. Other components interfere with oculomotor assessment. Specifically, accommodative divergence interferes with tonic vergence estimation and the type of accommodation considered in the AC/A ratio affects its magnitude. Results on clinical tonic accommodation and clinical CA/C show that further investigation is needed to clarify the limitations associated with the use of difference of Gaussian as visual targets to open the accommodative loop. Conclusions Although different optometric tests of accommodation and vergence rely on the same basic principles, the results of this study indicate that clinical and laboratory methods actually involve distinct components. These differences, which are induced by methodological choices, must be taken into account, when comparing studies or when selecting a test to investigate a particular oculomotor component.